Pengembangan Model Pembelajaran ILC3 Pada Mata Kuliah Seminar PAUD - Isa Hidayati; Sariana Marbun; Dwi Septi Anjas Wulan; Resti Citra Dewi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to develop the ILC3 learning model in seminar courses. This study uses a 4-D development model consisting of 4 stages, namely defining, planning, developing and disseminating. The ILC3 learning model is used to develop students' 21st century skills. The product produced in this study is a guidebook for using the ILC3 learning model in seminar courses.The results of the study show that the Syntax of the ILC3 learning model, namely Identify, Literature review, Construct, Create, and Communicate, is valid for use in seminar learning with an average of 84.6% with a very valid category. The ILC3 learning model is practically used in seminar learning, these results are in accordance with data analysis in small group tests which show an average of 85.9 in lecturer responses indicating very practical, an average student response of 87.8 indicating very practical, an average student ability result of 84.1 in the very practical category. The results of the large group test showed an average of 87.4 in lecturer responses indicating very practical, an average student response of 88.5 indicating very practical, an average student ability result of 88.5 in the very practical category. The ILC3 learning model is effective in seminar learning as seen from the results of student tests. in the small group test it has a Ngain value of 0.8 with a high category. Meanwhile, in the large group test, the Ngain value was 0.9 with a high category.